Practicality of Story-Based Religious Development Materials in Class II A Padang Correctional Institution - Antoni Haikal; Ahmad Sabri; Gusril Kenedi (Tarbawi : Jurnal Ilmu Pendidikan, 2025)
The purpose of this research is to see the Practicality of Story-Based Religious Development Materials in the Correctional Institution class II A, Padang. This research is part of R & D research. To see the practicality of the product in the form of story-based coaching materials in class II A, Padang correctional institutions.  The method used is experimentation. The instrument used is a questionnaire to see the practicality of the coaching material. The research sample was Block A prisoners at Class II A Padang Correctional Institution. Practicality in development refers to the extent to which a developed product can be implemented and used effectively. At this stage, a trial was conducted to see the practicality of using the story-based coaching material that had been designed. The results showed that story-based religious guidance material in correctional institutions is highly practical for prisoners, as evidenced by practicality test scores obtained during the trial. Its coaching material, developed in a highly practical category, achieved an average score of 83.29%. Trial II obtained a result of 86.64% very practical category